Implementing the Action Plan for Energy Access Scale-Up in Africa - World Bank (Washington, DC, 2013)
The action plan has the target of increasing the percentage of households with electricity access in Sub-Saharan Africa from 25 percent in 2005 to 35 percent in 2015 and 47 percent by 2030. The plan noted that this target is feasible if countries improve their sector policies and implementation capacity and concessional financing doubles from US$2 billion to US$4 billion annually. The action plan emphasizes the importance of country leadership in developing national energy sector strategies, as well as the need for harmonization, alignment and coordination of donor support in line with the principles of partnership set out in the 2005 Paris declaration on aid effectiveness. The plan notes that enhancement of government's oversight and regulatory role will be keys and it emphasizes the role of the private sector both as a source of investment and for its technical and managerial know-how. Improved governance and private sector participation are both needed in bringing about efficiency improvements in the energy sector. The study was designed to be catalytic-i.e. to identify a shortlist of projects with transformational potential and then, in follow-up phase, to identify the critical preparatory work needed to move each project forward.